2012
DOI: 10.1136/bmj.e3054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tranexamic acid on surgical bleeding: systematic review and cumulative meta-analysis

Abstract: Objective To assess the effect of tranexamic acid on blood transfusion, thromboembolic events, and mortality in surgical patients.Design Systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
608
3
25

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 820 publications
(674 citation statements)
references
References 141 publications
17
608
3
25
Order By: Relevance
“…The two most commonly used doses of TXA are 1 g bolus followed by 1 g over 8 h (from the CRASH-2 trial) and 1 g bolus followed by 10 mg/kg/hr in liver transplantation studies. 27,43 In a meta-regression analysis, the effectiveness of TXA was stable over a wide range of doses, suggesting that the impact of TXA is not dose-dependent at the concentrations used clinically. In contrast, more complications (most notably seizures) were observed at higher doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two most commonly used doses of TXA are 1 g bolus followed by 1 g over 8 h (from the CRASH-2 trial) and 1 g bolus followed by 10 mg/kg/hr in liver transplantation studies. 27,43 In a meta-regression analysis, the effectiveness of TXA was stable over a wide range of doses, suggesting that the impact of TXA is not dose-dependent at the concentrations used clinically. In contrast, more complications (most notably seizures) were observed at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis of 95 surgical randomized controlled trials (N = 7838 patients), TXA reduced the probability of receiving a blood transfusion by one third (risk ratio 0.62, 95% confidence interval 0.58 to 0.65; p < 0.001). 43 The majority of these trials were in cardiac and orthopedic surgery however, where the mechanism of bleeding is significantly different than abdominal surgery. Four small trials have been performed in patients having liver transplantation; TXA did not result in significant reduction of allogenic blood transfusion, although the confidence interval was wide and there was a trend towards improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Méthode Nous avons mis en oeuvre une politique de qualité des soins afin de procéder à l'administration universelle de TXA par voie intraveineuse à une dose de 20 mgÁkg -1 à tous les patients admissibles subissant une arthroplastie totale de la hanche ou du genou entre le 21 Administration of tranexamic acid (TXA) has been shown to reduce blood loss and allogeneic red blood cell (RBC) transfusion in cardiac and various noncardiac surgical procedures. 1 Many randomized controlled trials, [2][3][4][5][6] systematic reviews, and meta-analyses [7][8][9][10][11] have shown that systemic and topically administered TXA reduces allogeneic RBC transfusion in hip or knee arthroplasty surgery. Recent observational studies have also shown an association between TXA use and reduced RBC transfusion.…”
Section: Résuméunclassified
“…More than 100 randomized controlled trials have demonstrated that intravenous tranexamic acid for surgical patients reduces the risk of receiving a blood transfusion by about one-third, but potential harms of systemic administration include pulmonary embolism, stroke, and myocardial infarction, each of which could be fatal [8]. Therefore, considerable research has recently focused on whether topical administration might offer similar efficacy with acceptable safety.…”
mentioning
confidence: 99%